Movable blade vertical shaft kinetic turbine visual observation - Lempoy, Kennie Abraham; Soenoko, Rudy; Wahyudi, Slamet; Choiron, Moch Agus (Eastern-European Journal of Enterprise Technologies, 2019)
Kinetic energy is the energy produced due to the river water flow speed. This water speed energy can be effectively implemented as a rural power plant. This research has been carried out experimentally and the research is under a laboratory scale research. The turbine tested is a vertical shaft kinetic turbine equipped with eight blades. This study is a continuation of the previous research, which is observed based on the turbine parameters. While in this research the observations are based on a visual test, namely observing the behavior of the water movement and blade movement in the turbine. The visual test is a test by observing the turbine blade movement and water behavior in the turbine area. From this visual test, it can be seen what is the caused of the low turbine efficiency and what is the causes of the unstable turbine rotation. From the visualization image observing, it is found that the water does not hit the turbine blade completely. The turbine blade opening time is a little bit too late, so that the water could not fully push the blade surface. At a certain blade position, the water flow is not entering the area between two blades, which results in a weak blade push. This means that there is a turbine torque reduction. From these explanations, it is found that these constraints are the points that result in the unstable turbine rotation. For a better turbine performance, it is suggested to add the turbine blade number. The more the blade number, the smaller the area between the two blades and the more effectively the water flow pushed the turbine blade. The turbine rotation would be more stable and the turbine efficiency would surely be higher